First Draft Genome Sequence of the Pathogenic Fungus Lomentospora prolificans (Formerly Scedosporium prolificans). Issue 11 (1st November 2017) - Luo, Ruibang; Zimin, Aleksey; Workman, Rachael; Fan, Yunfan; Pertea, Geo; Grossman, Nina; Wear, Maggie P; Jia, Bei; Miller, Heather; Casadevall, Arturo; Timp, Winston; Zhang, Sean X; et al.
Abstract: Here we describe the sequencing and assembly of the pathogenic fungus Lomentospora prolificans using a combination of short, highly accurate Illumina reads and additional coverage in very long Oxford Nanopore reads. The resulting assembly is highly contiguous, containing a total of 37, 627, 092 bp with over 98% of the sequence in just 26 scaffolds. Annotation identified 8896 protein-coding genes. Pulsed-field gel analysis suggests that this organism contains at least 7 and possibly 11 chromosomes, the two longest of which have sizes corresponding closely to the sizes of the longest scaffolds, at 6.6 and 5.7 Mb.